Regio- and stereoretentive synthesis of branched, linear (E)- and (Z)-allyl fluorides from allyl carbonates under Ir-catalysis - Benedetto, E; Tredwell, M; Hollingworth, C; Khotavivattana, T; Brown, J; Gouverneur, V (2013)
This paper describes a new catalytic method for the regio- and stereocontrolled fluorination of allylic carbonates. This transformation uses TBAF·4tBuOH as the fluoride source and [Ir(COD)Cl]2 as the catalyst; the most commonly used [Ir(COD)Cl]2/phosphoramidite system is ineffective. Synthetically, this reaction is characterized by a high degree of structural conservation in going from substrates to the products. The fluorination of (E)-allylic carbonates leading to linear (E)-allylic fluorides (l : b > 20 : 1, E : Z > 20 : 1) is unprecedented and a unique feature of fluoride as the nucleophile. The first examples of transition metal catalyzed fluorination affording (Z)-allyl fluorides (Z : E ratio >20 : 1) are disclosed along with the successful fluorination of branched, linear (E)- and (Z)-allyl carbonates with [18F] fluoride in the presence of [Ir(COD)Cl]2. 18O-Labeling of the reactant reveals internal return during the allylic ionization step, and pathways for effective intra- and intermolecular isotope exchange. © 2013 The Royal Society of Chemistry.